Pengaruh Jalan Santai Terhadap Tekanan Darah Pada Pra-Lansia Di Posyandu Lansia Sejahtera Abadi Ix Candi Baru - Saputro, Nugroho Dwi, dr. Sigit Widyatmoko, Sp. PD, M. Kes, dr. Safari Wahyu Jatmiko (2015)
Background : Often we see the community come to the health facility just to know their blood pressure. One of the terrible scourge to society is hypertension. Hypertension is a problem in the elderly because it can be a risk factor for stroke, heart failure and coronary heart disease. Systolic pressure is the blood pressure when the sound of the first kortokoff reads while diastolic pressure is the pressure at the time of the last kortokoff sound rang. One of the factors that affect blood pressure is physical activity. Physical activity is body movement produced by skeletal muscles that requires energy. Purpose : Knowing the influence of walking to changes in blood pressure in elderly participants Sejahtera Abadi IX intesife health care, Candi Baru. Method : This study is observational analytic quasi-experimental approach. The study involved 68 respondents to the characteristics of the sample were classified as pre elderly (45-59 years), not smoking and not suffering from malignancy. Sampling taken with purposive sampling technique. The measuring instrumen is tAutomatic blood preasure monitor and list DASS statement. Paired t-test and Pearson correlation used to analyse the data . Result : the research of this experiment obtained the p-value paired t test p <0.05 and p value at Pearson test p = 0979, which means statistically significant, so there is a walking effect on blood pressure in pre-elderly in the Elderly Sejahtera Abadi IX intensife health care, Candi Baru Conclusion :there is an effect on blood pressure of walking on a pre elderly in Sejahtera Abadi IX elderly intensife health care, Candi Baru with a statistically significant difference and the strength of the correlation is very strong.